The Problem of Older People Welfare from the Value Approach Perspective; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 7 : Lifelong Wellbeing in the World (WELLSO 2015) - Ivankina L. I. Lyubov Ivanovna (2016, 2016)
Title screen